Studi Komparatif Konsep Pendidikan Islam K.H. Ahmad Dahlan dan Muhammad Fethullah Gülen - Estetika, Rio; , Dr. Mohamad Ali, S.Ag.,M.Ag (2016)
Islamic education is considered only to be oriented to the hereafter, to teach rituals of worship and develop a defensive posture against the negative influence of Western culture. On the other side, Islamic education is faced with the phenomenon of discontinuity value experienced by Muslims, which begins with waning respect for the basic values and ethics, such as honesty, discipline, tolerance. It encourages K.H. Ahmad Dahlan and Muhammad Fethullah Gülen to innovate and develop an ideal Islamic education. This study aims to understand the concept Islamic education of K.H. Ahmad Dahlan and Muhammad Fethullah Gülen, how to aplicate, how to compare. This type of research is the study of literature with historical and philosophical approach. Islamic education for K.H. Ahmad Dahlan is integralism between theology and science, tolerance, open to modernity, and the perfection of education of the mind for the realization of human roles with functions to implement Islam in truth. Education ideas of Fethullah Gülen are based on the manifestation in the name of Allah, the emphasis on ethics education, science, and theology. In praxis, developed through a process of tarbiyah (character development), ta'līm (teaching science), it is combined with a variety of modern disciplines. The concepts of Islamic education of K.H. Ahmad Dahlan and Fethullah Gülen have similarity in common: (1) the idea / notion of education, which integrates religion with science and open to modernity; (2) the source and basis of education, namely the Qur'an and Hadith, as well as the fundamental values; (3) educational purposes, namely to realize individual character, master of science (science), and help the stundents to have commitment to fight for the interests of Muslims; (4) educational methodology, the approach of contextual methods, modeling, advice, and student centered. The difference between the two concepts of Islamic education: (1) educational materials, namely in education of K.H. Ahmad Dahlan widely teach basic sciences of religion combined with general knowledge. While the dominant educational materials of Fethullah Gülen are on science teaching combined with universal values contained in the Al-Quran and Hadith; (2) educational institutions, K.H. Ahmad Dahlan developed madrasah education institutions with classical learning system. Fethullah Gülen developing dormitory (boarding school) education models and implement has moving classsystem. Islamic education of K.H. Ahmad Dahlan is excellent in religious education materials that cover all religious dimensions (ideological, ritual, consequential, and intellectual). Later Islamic education of Fethullah Gülen is superior in the spread of educational institutions and science competition. Key Words: Islamic Education, K.H. Ahmad Dahlan, Fethullah Gülen